Janusz Korczak, (2023). Sam na Sam z Bogiem. Modlitwy tych, którzy się nie modlą. Warszawa: Wydawnictwo Więź, ss. 99 - Rudnicki, Zbigniew (Studia Edukacyjne, 2023)
Recenzja: Janusz Korczak, (2023). Sam na Sam z Bogiem. Modlitwy tych, którzy się nie modlą. Warszawa: Wydawnictwo Więź, ss. 99